1999
DOI: 10.1016/s0035-9203(99)90048-2
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide-treated materials for malaria control in Latin America: to use or not to use?

Abstract: Studies on the protective efficacy of insecticide-treated materials (ITMs) in Plasmodium vivax endemic areas of Latin America have not yielded sufficient evidence for recommendation of their extensive use in the region. Therefore 2 randomized community trials have been conducted on the Pacific Coast of Nicaragua which analysed the minimum coverage of ITMs needed to be effective against malaria. For the characterization of the study area, epidemiological and entomological baseline surveys and household intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 17 publications
0
33
1
Order By: Relevance
“…The effectiveness of insecticide-treated mosquito nets varies with the rate of malaria transmission; the nets do not work well in many areas of low and unstable transmission, where malaria vectors bite in the early evening and morning. 23 Further work remains to be done on new combinations of insecticides and fabrics. More information is also needed on the relation between the extent of community use of insecticide-treated mosquito nets and malaria morbidity, mortality, and transmission.…”
Section: Prevention Of Infectionmentioning
confidence: 99%
“…The effectiveness of insecticide-treated mosquito nets varies with the rate of malaria transmission; the nets do not work well in many areas of low and unstable transmission, where malaria vectors bite in the early evening and morning. 23 Further work remains to be done on new combinations of insecticides and fabrics. More information is also needed on the relation between the extent of community use of insecticide-treated mosquito nets and malaria morbidity, mortality, and transmission.…”
Section: Prevention Of Infectionmentioning
confidence: 99%
“…Insecticide-treated materials (ITMs) have a mean protective efficacy against malaria episodes of roughly 50% in highly endemic areas of Africa [1] and of 40% in lower endemicity areas of Latin America where either P. vivax or P. falciparum are predominant [2,3]. Other trials have shown that ITMs are also protective against the transmission of Chagas' disease [4] and of cutaneous leishmaniasis [5] making them one of the most powerful weapons against disease-transmitting vectors.…”
Section: Introductionmentioning
confidence: 99%
“…Application of the repellent DEET to ankles and feet of the population in an African village significantly reduced the incidence of malaria (Durrheim and Govere 2002). Repellent soaps that contain DEET and permethrin have been shown to successfully reduce malaria infections (Kroeger et al 1997, Kroeger et. al., 1999).…”
mentioning
confidence: 99%